Reverse conducting–IGBTs initial snapback phenomenon and its analytical modelling. Issue 3 (1st May 2014) - Vemulapati, Umamaheswara; Kaminski, Nando; Silber, Dieter; Storasta, Liutauras; Rahimo, Munaf
Abstract : Analytical models have been proposed to describe the onset current density for the initial snapback in the transistor on‐state mode and in the blocking state of reverse conducting‐insulated gate bipolar transistors (RC‐IGBT) for the stripe and cylindrical designs of the anode shorts. In cylindrical case, there are two possible ways in designing the anode shorts and the authors have proposed an analytical model for each of them. The considered RC‐IGBTs are vertical with soft punch‐through type buffer designs. The analytical model has been evaluated with the aid of 2‐D device simulations and measurements. The authors have investigated the initial snapback phenomenon for different voltage class devices at a given technology (anode and buffer profiles) and found out that the snapback voltage increases with the blocking capability but not the snapback current density. The authors have also observed that the initial snapback phenomenon is more pronounced at lower temperatures. From the analytical model as well as simulation and measurement results, the authors have found that for a given voltage class and technology, the p + ‐anode width is the only remaining design degree of freedom which determines the initial snapback. The adjustment of the on‐state losses can then be done with the proportion of the n + ‐short region.